Peningkatan Hasil Belajar Peserta Didik pada Pembelajaran Pendidikan Pancasila Menggunakan Model Cooperative Learning Tipe Scramble di Kelas V SDN 13 Guguak Randah Kabupaten Agam - Putri, Silva Rahma; Waldi, Atri; Amsari, Dina; Reinita, Reinita (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to describe the improvement in student learning outcomes using the scramble type cooperative learning model in the Pancasila Education subject class V at SDN 13 Guguak Randah Agam District. This research is Classroom Action Research (PTK) using a qualitative and quantitative approach carried out in two cycles. The subjects in this research were 20 class V students at SDN 13 Guguak Randah in the January-June semester of the 2024/2025 academic year. Research data consists of the results of observations of teaching modules, results of observations of teacher and student activities, as well as student learning outcomes using the Scramble type cooperative model. Data collection techniques use observation or observation, test and non-test. The data was analyzed in a quantitative descriptive manner. The results showed improvement in various aspects. The teaching module increased from 87, %(Good) in cycle I to 97% (Very Good) in cycle II. Teacher activity increased from 83,5% (Good) to 96% (Very Good), while learner activity increased from 83,5% (Good) to 96% (Very Good). The learning outcomes of students also increased, with an average score from 76,9 (enough) in cycle I to 91,3 (Very Good) in cycle II. It can be concluded that the Scramble type Cooperative Learning model can improve student learning outcomes in class V Pancasila Education subjects at SDN 13 Guguak Randah, Agam District.